An outcast from the team: Exploring youth ice hockey goalies' benching experiences. (September 2018) - Battaglia, Anthony; Kerr, Gretchen; Stirling, Ashley
Abstract: Objectives: Anecdotal evidence suggests that youth may experience negative outcomes when benched, such as a lack of fun and intentions to quit (Frank, 2013; O' Sullivan, 2015). In the sport of ice hockey, it is speculated that amongst position players, including goalies, forwards, and defenders, the negative effects of benching may be exacerbated for goalies, presumably due to the public manner in which the benching takes place (Hertz, 2010, 2013). The purpose of this study therefore was to examine competitive youth ice hockey goalies' experiences of benching as a result of not playing well during a game. Methods: Data were collected through semi-structured interviews of seven male competitive youth ice hockey goalies between the ages of 13–15 years. Data were analyzed using a thematic narrative approach (Riessman, 2008; Smith, 2016). Results: Participant stories suggest that benching can be detrimental to an athlete's feeling of self-worth and relations with coaches and teammates when experienced as a form of punishment. Across all of the goalies' stories, notions of feeling like an outcast on their team after experiencing benching were articulated. Four overarching narratives were developed from their stories: the skate of shame, the banished bench, the lonely locker room, and the silent celebration. Conclusions: This study advances current youth sport literature as it is one of the first to examine youth athletes' benching experiences empirically. Recommendations for future research and practice are suggested. Highlights: This study explored youth ice hockey goalies' benching experiences during a game. Benching was considered a punishment by all goalies. Benching negatively impacted the goalies' self-worth and sport relations. The negative outcomes of benching share similarities with time-out practices. The results may be used to inform strategies for diminishing the potential negative experiences associated with benching.